Social Inequality - Warwick-Booth, Louise; Warwick-Booth, Louise (SAGE Publications, 2022)
This book provides up to date discussion and evidence about inequalities, social divisions and stratification. Its innovative style engages readers and encourages them to reflect upon the many dimensions of social inequality. This updated third edition contains: Three new chapters on employment, sexualities and migration Updated coverage of intersectionality throughout Thirteen new in-depth case studies (one per chapter) This is a must read as a key introductory companion for students who wish to understand the dynamics of contemporary social inequality. Louise Warwick-Booth is a Reader at the School of Health, Leeds Beckett University